Numerical Simulation of Slope–Gully–Stream Sediment Transport Process with Water and Gravity Erosion - Liu, Yan; Yang, Zhenyu; Wang, Xiekang (Frontiers in Earth Science, 2022)
Soil erosion has become a global problem and the subsequent influences are serious. It is the source of the sediment in river and the sediment transport after it is complicated. Water erosion and gravity erosion, as common forms of soil erosion, have different subsequent sediment transport processes along slope-gully-stream. Numerical simulation can reflect these processes well under different sediment yield types. This paper applies CFD-DEM method to study the sediment transport after water erosion and gravity erosion. During the sediment transport process, the solid-phase particles in the gravity erosion case move at a larger speed in the initial stage. A decrease of particle velocity on the slope occurs due to accumulation in water erosion cases. The streamwise velocity distribution of liquid phase conforms to the logarithmic distribution before the sediment transport process starts. Influenced by the solid phase particles, the flow velocity near the bottom decreases significantly. The sediment transport rate peak in gravity erosion cases is larger than water erosion cases. In water erosion cases, when the slope is steep, there is no peak in the sections located at the inlet and outlet of gully. The sediment transport rate of the sections in river shows a step-form in declining process.